Implementasi Literasi Al-Qur’an dalam Pembinaan Karakter Religiusitas Peserta Didik pada SMA/SMK di Kabupaten Sidenreng Rappang - Ummul Hidayatullah Syarifuddin; Munir Munir; Hasyim Haddade (Universitas Muhammadiyah Makassar, 2021)
The main problem discussed in this research is the implementation of Al-Qur'an literacy in fostering the religious characters of SMA/SMK students in Sidenreng Rappang Regency. To address to the aforementioned problems, the researcher used several approaches namely pedagogic, historical, and sociological approaches. The sources of data in this research consisted of primary and secondary research data. The data were obtained from books, literature related to the topic, and other supporting documents. The research instrument of this research was the researcher himself as the key instrument. In addition, the researcher further developed new instruments such as observation guidelines, interview guidelines, and documentation. All three instruments were used to collect data in the research field. The results of this study indicated that the implementation of Al-Qur'an literacy carried out at SMA/SMK in Sidenreng Rappang has been in the forms of 15-minute Al-Quran recitation and tadarrus and Kultum activity. The activities have been conducted regularly on Friday. In terms of the opportunities, there are two factors influencing the program implementation namely the internal and the external factors. For the internal factors, it was evident that the program has been supported by the school principal. Other internal factors were the availability of competent teachers, adequate facilities, and the Al-qur’an to be owned by all students. All those factors have helped the successful implementation of the program. For the external factors, it was suggested that the local government has involved in supporting the program. For example, the provincial government has regulated to obligate schools to implement Al-qur’an literacy program in schools. However, despite some opportunities, a number of obstacles has been found. The problems such as the minimal allocation of time given to run the program and the inabilitiy of students to read the Al-Qur’an have appeared during the implementation of the program. Besides, the students did not seem to be aware of the literacy program implemented in schools. Therefore, the Al-Qur’an literacy program could not be implemented optimally. Despite the problems, decent religious characters could be instilled on some students such as honesty, responsibility, discipline, and care.